Perceptions of impacts and management of invasive alien plants: a case study from Mirzapur, India - Kumar, Sudhanshu; Meena, Renu; Tiwari, Amit Kumar; Singh, Rinku; Patel, Sanoj Kumar; Singh, Gopal Shankar (Frontiers in Forests and Global Change, 2023)
Invasive alien plants (IAPs) have become a serious threat to biodiversity, agriculture and socioeconomic development. Several aspects, including the ecological and economic impacts of IAPs have been explored in the recent past, however, perceptions of ecosystem services (ES) and ecosystem disservices (EDS) have not been well studied. IAPs affect the lives of local people both positively (providing ES) and negatively (providing EDS). IAPs in this region have not been studied through the aspects of ES and EDS that integrate the views and perceptions of local communities.Keeping in view this research gap, the present study was conducted in the Mirzapur district (Uttar Pradesh, India) where IAPs are widely distributed. In five sites covering a rural to urban gradient with increasing distance from forest, we randomly selected 100 respondents -20 from each of the five sites for the survey. A semi-structured questionnaire was used to collect respondents' perceptions on ES and EDS supplied by IAPs in their local habitats. The questionnaire was designed to obtain data on awareness and knowledge, perceptions of ES and EDS, attitudes toward management, and socio-demographic information. Results indicated that 95% of respondents were familiar with at least one of the 12 IAPs identified as being important in the region. Ipomea carnea and Stylosanthis hamata were the most and least frequently cited plants, respectively. Medical use and reduction in soil fertility were most perceived as ES and EDS, respectively. The value of Spearman's rank correlation coefficient (Spearman's ρ = 0.487, p > 0.05) indicates a nonsignificant correlation between ranks of ES and EDS cited by respondents. Older and less educated people were more aware of the impacts of IAPs. Uprooting was the most commonly used management practice to control the invasion of plant species. People's attitudes towards the management of IAPs seem to indicate that they prefer to eradicate species that have direct harmful effects on human health and biodiversity. This study provides inputs for incorporating people's perceptions into the control and management of IAPs in the forest region.